Pengaruh Penyuluhan Kesehatan terhadap Tingkat Pengetahuan Perilaku Hidup Bersih dan Sehat (PHBS) - Putri, Rima Eka; Adriyanti, Sri Lestari; Hidayanti, Rahmi; Wijayantono, Wijayantono; Nur, Erdi; Marza, R. Firwandri (Jurnal Kesehatan Lingkungan Mandiri, 2025)
Improved knowledge of Clean and Healthy Behavior (PHBS) in schools can be acquired through health education. Education can help enhance one’s knowledge. One of the activities in health education is dissemination using interesting learning media, such as media booklets. The aim of this study is to determine the impact of health dissemination on the level of knowledge of clean and healthy life behavior (PHBS) students in MTSN 6 Kerinci Year 2023. This type of research is analytical research with an experimental design. This is a one-group pretest-posttest design. The population and sample of the study consisted of 63 respondents. Univariate and bivariate data analysis with correlation tests The results of the study obtained a p value (P Value) for knowledge before and knowledge after given health certification of 0,000 indicating that there is a significant influence of medical certification on the level of knowledge of Clean and Healthy Behavior (PHBS) students in MTSN 6 Kerinci in 2023. Health education has a significant impact on improving the knowledge of Clean and Healthy Living Behavior (PHBS) among MTsN 6 Kerinci students. This is evidenced by the increase in the students’ average knowledge score from 60.16 before the education to 84.29 after, with a p-value of 0.000 (<0.05). It is recommended that students continue to develop awareness in applying clean and healthy living behaviors within the school environment.